YUMIF dan Perubahan Sosial: Karakter, Komunikasi Strategis, dan Aktivasi Keterlibatan - Abdul Rohman (Jurnal Komunikasi, 2014)
Middle class in Indonesia is growing up but its interest is still inadequate in the political arena as the poor and the have. Mobilizing middle class to voice out their aspiration can trigger social change that might contribute to shift the horizon of democracy in the country. This paper brings preliminary conclusion on this issue: a) Indonesian middle class hypothetically falls into transitional spectrum between baby boomers and early millennial that is indicated by the essential meaning of family and self-sufficiency in their career, embracing short-medium orientation, and inclination to be rational in responding communication message compared to earlier generation (b) fit and multidirectional communication strategy, emphasizing on engagement and dialogue via effective communication channels to yield collaborative exchange are necessary, and (c) Indonesian YUMIF has strong economic-political power to bring social changes, therefore, empowering them to bring a better Indonesia is crucial.